Age trajectories of disability development after 65: A comparison between Japan and Taiwan. (September 2021) - Chiu, Ching-Ju; Chen, Yun-An; Kobayashi, Erika; Murayama, Hiroshi; Okamoto, Shohei; Liang, Jersey; Jou, Yuh-Huey; Chang, Chia-Ming
Highlights: Older adults generally do not report ADL limitation until 77 years old, and mobility limitation occurs at a various age in Taiwan and Japan. Older adults generally do not face serious disability until 85 or 86 years old in Taiwan or Japan, respectively. The speed of disability with age for older adults Taiwan was faster than Japan in ADL and IADL limitation, but not in mobility. Abstract: Introduction: Disability development using age as the axis was void in the literature. Identification of the age trajectory of disability development across populations enables preparation for aging-related policies when conducting cross-national comparisons. This study compared three indicators of the development of physical disability in populations of Taiwan and Japan. Methods: Data comprised two nationally representative panel surveys (1) the Taiwan Longitudinal Study on Aging ( N  = 3, 037) in 1996–2011 and (2) the National Survey of the Japanese Elderly in 1996–2012 ( N  = 1, 974). Older adults (65+) were examined longitudinally. Activities of daily living (ADL), instrumental activities of daily living (IADL), and mobility disability development during aging were analyzed using multilevel models. Results: After age standardization, Japan reported higher prevalence rate of ADL disability (14.95% vs. 9.65%) but lower IADL (19.30% vs. 30.36%) and mobility disability (36.07% vs. 49.82%) as compared with Taiwan. ADL limitation occur (ADL limitation>=1) at the age of 77.9 and 77.2 for populations in Japan and Taiwan, respectively. Populations reached three ADL limitations at the age of 86.7 and 85.0 in Japan and in Taiwan, respectively. IADL limitation occur (IADL limitation>=1) at the age of 79.1 and 74.5 for populations in Japan and Taiwan, respectively. Mobility limitation occur (Mobility limitation>=1) at the age of 70.7 and 65.3 for populations in Japan and Taiwan, respectively. Conclusions: Older adults generally do not report ADL limitation until 77 and do not face serious disability until 85 or 86 in Taiwan or Japan, respectively. Mobility limitation occurs at a various age in different countries.